Sn-metrizable spaces and related matters. (3rd October 2005) - Luo, Zhiming
Abstract : We give a mapping theorem ons n -metrizable spaces, discuss relationships among spaces with point-countables n -networks, spaces with uniforms n -networks, spaces with locally countables n -networks, spaces withσ -locally countables n -networks, ands n -metrizable spaces, and obtain some related results.